Analisis Preferensi Konsumen dan Profil Pembeli di Industri Otomotif: Studi Kasus Pembelian Kendaraan di Wilayah Jabodetabek - Puspita, Angela Candra; Setiawan, Budi; Ayu, Cita; Heikal, Jerry (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to analyze consumer preferences for car models in the Jabodetabek area using K-Means Clustering technique with the assistance of SPSS program. Data were collected through distributed questionnaires covering demographic information, car usage habits, selection criteria, and preferences for car features. The questionnaires were distributed online to reach various segments of the population aged 23 and above who have an interest or intention to purchase a car. The collected data were analyzed using SPSS to identify consumer groups with similar characteristics. The analysis results show that the seventh cluster is the main target of the automotive four-wheel vehicle market in Jabodetabek, formed from seven clusters of several consumer segments with different preferences for car models and features. These segments can be used by the automotive industry to develop more effective and targeted marketing strategies. The research findings provide valuable insights into consumer preferences in Jabodetabek, which can help car manufacturers and dealers improve customer satisfaction and loyalty. Additionally, the results of this research can also serve as a reference for further research in the fields of marketing and consumer data analysis.